Iraq and the use of force in international law - Weller, M. (Marc); Lauterpacht Research Centre for International Law. (Oxford : Oxford University Press, 2010)
One million people in the UK alone demonstrated against the 2003 invasion of Iraq. A crucial element of the opposition to the war was the lack of a clear legal basis. This is the first book to analyze the lawfulness of the use of force against Iraq on the basis of formerly classified material made public by the official UK inquiry into the war.
Published under the auspices of the Lauterpacht Centre for International Law in the University of Cambridge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Iraq War, 2003- -- Law and legislation; Persian Gulf War, 1991 -- Law and legislation; Intervention (International law); Law; Great Britain -- Foreign relations -- Law and legislation